A review of continuous professional development in school principal carrier - Aan Komariah, Dedy Achmad Kurniady (Opción, 2019)
This research analyzes the formulation and implementation of principal continuous professional development and its effects on leadership capacity building. This policy analysis research is conducted by using the Stake’s Countenance Evaluation Model evaluation method. Research findings show that the policy is managed to encourage the principal to follow self-development, scientific publication and innovation works. In conclusion, types of professional building are yet specifically addressed to leadership capacity building, also its implementation is yet structured and continuous.